Diagnostic Performance of Digital Radiograph and Low-Dose Computed Tomography for the Diagnosis of Fishbone Retention in the Oropharynx - Chansangrat,Jirapa (2022)
Abstract Introduction Fishbone foreign body retention is one of the most common problem with various clinical manifestations from asymptomatic, abscess formation, and perforation to mediastinitis with subsequence morbidity and mortality. Accurately identifying the location of the fishbone leads to precise removal, which, in turn, prevents serious consequences. Digital radiographs have been widely used for diagnosis, but many studies show poor sensitivity. Object The present study was designed to compare the diagnostic performances of digital radiograph and low-dose computed tomography (CT) for fishbone retention and to demonstrate the radiation dose of the two modalities. Methods We collected 2 pieces of fishbone from each of the 15 species commonly eaten in Southeast Asia. We embedded each fishbone in a fresh pig’s neck, then subjected the pig’s neck to lateral soft tissue neck digital radiograph. The locations to embed included tonsil, base of tongue, and upper esophagus. Then, we subjected the same specimen to a CT scan. Two experienced radiologists interpreted each image. Results Visibility in the digital radiograph group was 13%, and in CT images group, it was 87% regardless of the locations. The average radiation dose from digital radiographs was 0.4 mGy (radiation dose field), while from CT images it was 8.6 mGy (CT dose index). Conclusion Most of the common fishbones in Southeast Asia could not be visualized by digital radiograph when embedded in the neck. Computed tomography scans demonstrated better diagnostic performance of fishbone retention compared to digital radiographs, regardless of the embedded location.